Carlyle Group's Taiwan Gambit. - Yu-Tzu Chiu (IEEE spectrum)
This paper presents news on the impending acquisition of the Taiwan-based Advanced Semiconductor Engineering Co. (ASE), the world's largest semiconductor assembly and testing services provider, by the Carlyle Group. The announcement that the U.S. investment group would buy ASE for the equivalent of US 5.5 billion prompted complaints about top Taiwan companies falling into foreign hands. The main concern has been whether rules governing transfer of sensitive technology to mainland China would be circumvented